Comparative Study of Ultrasonographic Findings with the Operative Findings of Biliary Surgery - A Study of 100 Cases - Hossain, Md Mosharraf; Rahman, Junaidur; Khandaker, Tawhida (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Ultrasonography (USG) of gallbladder and biliary system has become the primary imaging modality for the diagnoses of pathologies there. However, its accuracy in the diagnosis of various pathologies of gallbladder and biliary system is still debated. The present study was undertaken to determine the accuracies of USG in the diagnosis of various pathologies of biliary system and associated structures. Methods: This descriptive cross-section study was conducted in the Department of Surgery, Sir Salimullah Medical College and Mitford Hospital (SSMC&MH), Dhaka, between February 2002 to January 2003. Patients with symptoms and signs related to biliary disease and supposed to requiring some form of biliary surgery were included in this study. Patients having chronic liver diseases were excluded from the study. A total 100 subjects were included. On obtaining ethical clearance from the Ethical Committee of Sir Salimullah Medical College and Mitford Hospital (SSMC&MH), Dhaka, data collection was commenced. All the sampled population were subjected to USG of whole abdomen followed by laparotomy/operative treatment. Peroperative diagnosis was taken as confirmatory diagnosis, against which accuracy of USG was evaluated. Result: The study revealed that biliary disease was common in the fourth decade of life and females were more often affected than the males (female-to-male ratio: 3:1). Pain the right hypochondriac region was the most common (93%) presenting symptom, which in most cases (74%) was associated with flatulent dyspepsia. In over half (54%) of the cases, the pain increased after fatty meal. Right hypochondriac tenderness was the predominant physical sign (40%) followed by clinical jaundice (15%). Gallbladder and liver were palpable in few cases. Mild to moderate anaemia was observed in majority (82%) of the cases and severe anaemia (Hb < 50%) in 3% cases. Majority (85%) had leucocyte count within normal range (8,000-11,000/cu-mm of blood). Fifteen percent patients had significant rise of serum bilirubin (> 10 mg/dl); of them two had serum bilirubin > 20 mg/dl with a diagnosis of carcinoma head of the pancreas and/or gallbladder. Ultrasonography diagnosed 4 cases as having choledocholithiasis. But 6 more cases of choledocholithiasis were detected during operation with a false positive rate being 49.4%. Gallstone was reported to have been present in 78 patients by USG; 76 of them were confirmed peroperatively. Sensitivity and specificity of USG for common bile duct stone in this study was 4% and 90% respectively. Conclusion: The sensitivity of USG in the diagnosis of gall-stone was found to be optimum and moderate in the diagnosis of cholecystitis. In the diagnoses of other pathologies of biliary system, its sensitivity is much lower. Neoplastic lesion of pancreas and soft tissue mass inside common bile duct are too difficult to diagnose by USG. However, its specificity in ruling out the diagnosis of gall-stone is extremely low, but appreciably high in excluding other pathologies of biliary system. Ibrahim Card Med J 2022; 12 (1): 52-57